Capacidade de inovação regional: o papel de instituições e empresas de base tecnológica em Juiz de Fora - Eduardo Gonçalves; Fremar Pereira Hauck Gavio (Nova Economia, 2009)
The starting point of this paper is the interrelation between learning, innovation, regional and local development in the “Knowledge or Learning Economy”. Along with the traditional economic factors that have been considered in the literature on regional development, other factors such as trust, co-operation, innovative networks, institutions and other elements that are immaterial produce the regional development in the context of the “Learning Economy”. The main aim of this paper is to investigate the attempts to build a collective and regional learning process by innovative, technology based, small sized enterprises, together with other institutions in the city of Juiz de Fora. It highlights the local institutional environment and the characteristics of some information and knowledge intensive firms, supported by the Regional Center for Innovation and Technology Transference at the Federal University of Juiz de Fora. Moreover, special emphasis is given to some evidence about co-operation, innovative networks and external sources of information that are used to innovate.